2011
DOI: 10.1007/s13197-011-0386-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of stability of binary sweetener blend (aspartame x acesulfame-K) during storage in whey lemon beverage

Abstract: In the present study, artificial sweeteners-aspartame, acesulfame-K and binary sweetener blend of aspartame x acesulfame-K were assessed for stability during storage in whey lemon beverage. A solid phase extraction method using C 18 cartridges was standardized for the isolation of aspartame, acesulfame-K and their degradation products in whey lemon beverage. HPLC analytical conditions were standardized over C 18 column for simultaneous separation of multiple sweeteners and their degradation products in sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
1
7
0
2
Order By: Relevance
“…The LOD and LOQ are presented in Table 1. The detection limit of APM was in accordance with Lawrence and Charbonneau (1988), George et al (2010) and Arora et al (2008Arora et al ( , 2010Arora et al ( , 2013 over C 18 column at 200 nm.…”
Section: Linearity and Sensitivitysupporting
confidence: 84%
See 2 more Smart Citations
“…The LOD and LOQ are presented in Table 1. The detection limit of APM was in accordance with Lawrence and Charbonneau (1988), George et al (2010) and Arora et al (2008Arora et al ( , 2010Arora et al ( , 2013 over C 18 column at 200 nm.…”
Section: Linearity and Sensitivitysupporting
confidence: 84%
“…APM was also stable in whey lemon beverage stored under refrigerated condition for 15 days (Arora et al . ) as the pH of whey lemon beverage varied between 3.70 and 3.85.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional intake of sweets sugar replacement by polyols and acesulfame K on the quality aspects of low fat cookie and further reported that supplementation with acesulfame-K increased sweetness and improved perceived flavour and general acceptance of cookies. Acesulfame-K has high degree of stability when exposed to heat; this makes it a versatile sweetener with potential use in a wide range of foods and beverages (Arora et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…인공감미료는 2종 이상을 혼합하여 사용할 수 있으며 대표적인 예는 삭카린나트륨과 싸이클라메이트(1:10)의 조 합이다 4) . 단독으로 사용 시 발생하는 특유의 쓴맛, 뒷맛 (aftertaste) 등의 단점을 보완해주고 단맛을 상승시켜주기 때문에 음료류를 비롯한 가공식품에 적용하기 위한 연구 가 다양하게 이루어지고 있다 [5][6][7][8][9] . .…”
unclassified